1983
DOI: 10.1017/s0022029900023025
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and coagulating properties of renneted milks from different breeds and species of ruminant

Abstract: The detailed chemical composition of 25 milks from different breeds of cow, sheep and goat were related to their properties of rennet clotting, coagulum development and syneresis at pH 6-4. Experiments in which concentrations of fat and whey proteins in milk were manipulated, and in which milks were homogenized at different pressures, were also carried out and the effects observed were related to the above processes.The composition of milks varied widely and many relations between concentrations of components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
89
1
21

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 31 publications
26
89
1
21
Order By: Relevance
“…The shorter coagulation time can be explained by the lower pH of the milk, as often observed [16]. The greater curd firmness of Mo cows' milk is essentially due to its higher nitrogen content, as observed by a number of authors [16,22] and confirmed herein. The higher curd firmness of Modicana milk with the same nitrogen content could be attributed firstly to the polymorphism of casein κ, as evidenced in individual [9] or mixed milks [14].…”
Section: Discussionsupporting
confidence: 80%
“…The shorter coagulation time can be explained by the lower pH of the milk, as often observed [16]. The greater curd firmness of Mo cows' milk is essentially due to its higher nitrogen content, as observed by a number of authors [16,22] and confirmed herein. The higher curd firmness of Modicana milk with the same nitrogen content could be attributed firstly to the polymorphism of casein κ, as evidenced in individual [9] or mixed milks [14].…”
Section: Discussionsupporting
confidence: 80%
“…Manual measurement [11]: Freshly prepared 1:10 diluted chymosin (Chymax Plus, Chr. Hansen, Hungerford, UK) was combined with milk at 0.03% (v/v) and incubated at 30°C.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The analyses included pH, titratable acidity, aroma, clots on boiling, ethanol stability and lactoperoxidase activity (Fweja et al, 2007). In addition, a bulked milk sample was prepared from the individual samples, for each of the four treatments, and these were then analysed for rennet clotting time (Storry et al, 1983) and total viable count (Marks et al, 2001).…”
Section: Cows Experimental Design and Dietsmentioning
confidence: 99%